An Effort to Lower Electricity Bill in University Building by Automatic Lighting Switches Application. - Martini; Riyanto, Indra; Adiyarta, Krisna; Suparmoko, M. (Pertanika Journal of Social Sciences & Humanities)
There is a high demand for electricity in Indonesia which results in spiralling cost of electricity. This is compounded by the fact that many power generators in Indonesia still use fossil fuels. Universitas Budi Luhur aims to be a green campus. One way to reduce demand for energy s to use the electricity efficiently and sparingly, such as turning off the lights in the rooms when they are not in use though this is difficult to be implemented in public spaces such as toilets. Automatic light switches were installed in sample toilet rooms from August 1, 2016 to August 6, 2016. The energy saving was quite substantial, and translated into a cost saving of IDR 52.157,40 per week (about 63% of total weekly usage) or IDR 207.628,50 per month or IDR 2.503.555,20 per year. With the assumption of similar usage in all six toilets, annual saving in the electricity bill is estimated to be IDR 15.021.331,20.